P5.028 Swab2know: Provide an Oral Fluid Sample on Site, Check Your HIV Test Result Online. (13th July 2013) - Platteau, T; Fransen, K; Nöstlinger, C; Albers, L; Manirankunda, L; Vermoesen, T; Florence, E
Abstract : Background: Despite the high testing rate in Belgium a considerable number of individuals remain undiagnosed. Outreach and minimally invasive strategies might increase the uptake of HIV-testing. Swab2know aims at evaluating the feasibility of a non-invasive and confidential HIV test strategy among groups with a high risk of acquiring HIV infection (Subsaharan African migrants; SAM, and men who have sex with men; MSM) in community settings. Methods: Swab2know is using oral fluid samples for HIV-testing. Oral fluid is collected on a validated device (Oracol ® ). Serologic HIV testing (Genscreen ® HIV-1/2 v2) and quality control (IgG determination) are performed at the Institute of Tropical Medicine's (ITM) AIDS Reference Lab. Participants: can choose to receive their result either through a secured website (www.swab2know.be ) or personal counselling. Reactive results are disclosed as indicative for HIV-infection, needing confirmation on blood using the gold standard tests. These participants are contacted by phone after they checked their result, offering confirmation tests or referral to a local HIV-treatment centre. In case of a non-reactive test, participants are offered repeated testing after four months by ordering an oral fluid sampling device kit online. Data on age, sex, origin, HIV-testing behaviour, and sexual activity are collected using a survey. Results: After 2.5 months, 166 participants were tested in 11 settings. Fifty-three were SAM (31.9%), 111 MSM (68.1%). Twenty-two SAM (41.5%), and all MSM (100%) chose to receive their result through the website. Nine participants tested positive for HIV: three SAM (5.7%), and 6 MSM (5.4%). Preliminary experiences show a high uptake, and good acceptance of sampling method, and online communication of test results. Conclusion: Preliminary experiences with this low-threshold method are promising, showing high acceptance and satisfaction with the online tool. Increasing uptake by ordering sampling devices online, is studied. Up-to-date results and more specific conclusions will be presented at the conference.